Efisiensi Biaya Penugasan Karyawan Dengan Metode Hungarian : Studi Kasus pada Konveksi RAPPI - Riani, Lilia Pasca; Laharjingga, Khesya Duhitawangi (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2024)
Research aim: This study aims to analyze the efficiency of employee assignment costs at Rappi Convection Company. Design/Methode/Approach: The research design is descriptive qualitative. The analysis technique is the Hungarian method, which consists of 9 completion steps. Research Finding : The results of this study indicate that by using the Hungarian Method, the Rappi convection company can save its employee assignment costs to Rp. 18,000 per piece of clothing. Theoretical contribution/Originality : This research provides new insights and valuable information to improve production cost efficiency, especially in employee assignment costs. Practitioner/Policy implication : The Hungarian method proves to be a very useful method in relation to production cost efficiency, especially in MSME-scale companies. Research limitation : although the results showed cost efficiency after being calculated using the Hungarian method, this research still cannot cover the cost efficiency of other components so that further research must be carried out in order to increase production cost efficiency in the Rappi convection company.